SURVIVAL FOE BETTER LIFE IN THE JUNGLE BOOK - Ezra Pongoh; Elisabeth Z Oroh; Agustine C Mamentu (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
This research aims at describing survival reflect by main character in The Jungle Book. The research is uses qualitative method. The data are taken from two sources: primary source is the novel itself that is The Jungle Book and the secondary source are books related with the topic and internet sources to support this research. In addition, the researchers use objective. The finding of this research shows that Mowgli has qualities of survive there are strategy, struggle and gratitude. It is described how the survive reflected in novel The Jungle Book. So, the lesson is about the more time to spend with them, the more the mutual understanding revealed and by that Mowgli more exist to spread his kindness and keep spirited to survive in his destiny (Jungle) for better life with a better purpose.